Mitochondrial transport in neurons and evidence for its involvement in acute neurological disorders - Lu, Dengfeng; Feng, Yun; Liu, Guangjie; Yang, Yayi; Ren, Yubo; Chen, Zhouqing; Sun, Xiaoou; Guan, Yixiang; Wang, Zhong (Frontiers in Neuroscience, 2023)
Ensuring mitochondrial quality is essential for maintaining neuronal homeostasis, and mitochondrial transport plays a vital role in mitochondrial quality control. In this review, we first provide an overview of neuronal mitochondrial transport, followed by a detailed description of the various motors and adaptors associated with the anterograde and retrograde transport of mitochondria. Subsequently, we review the modest evidence involving mitochondrial transport mechanisms that has surfaced in acute neurological disorders, including traumatic brain injury, spinal cord injury, spontaneous intracerebral hemorrhage, and ischemic stroke. An in-depth study of this area will help deepen our understanding of the mechanisms underlying the development of various acute neurological disorders and ultimately improve therapeutic options.